Analisis Pengaruh Penggunaan Aplikasi Quizizz Berbasis Teknologi Smart TV dalam Meningkatkan Minat Belajar Siswa di Kelas VB SD Inpres Bumi Sagu - Muhamad kausar Lukman; Khairunnisa; Gita Ismi Nuraini; Ananda Karina; Fatma Aina (JURNAL DIKDAS, 2026)
This study aims to determine the effect of using Smart TV technology combined with the Quizizz application on increasing student interest in mathematics in grade VB of SD Inpres Bumi Sagu. The background of this study is based on low student interest in mathematics, which is often perceived as difficult and uninteresting. Therefore, innovative technology-based learning media are needed to increase student engagement in the learning process. This study used a quantitative approach with a simple experimental method. The subjects were 8 grade VB students at SD Inpres Bumi Sagu. Data collection techniques used a learning interest questionnaire, observation, and documentation. The data obtained were then analyzed using descriptive statistics to determine changes in student interest before and after the use of the learning media. The results showed that the use of Smart TV technology through the Quizizz application increased student interest in mathematics. This was evident in the increased enthusiasm, active participation, and interest of students during the learning process. Furthermore, the engaging visual display, game elements, and direct feedback from the Quizizz application increased student motivation to participate in the learning process. Thus, it can be concluded that the use of Smart TV technology media based on the Quizizz application has a positive influence on increasing students' interest in learning mathematics in class VB SD Inpres Bumi Sagu.